ECMO-induced coagulopathy: strategic initiatives for research and clinical practice (a workshop report of the NHLBI) - Jerrold H. Levy; Peta M. A. Alexander; Alisa S. Wolberg; Owen J. T. McCarty; Anthony E. Pusateri; Raquel R. Bartz; Wolfgang Bergmeier; Mitchell J. Cohen; Jean M. Connors; James H. Morrissey; Matthew D. Neal; Elisabeth T. Tracy; et al. (Blood Vessels, Thrombosis & Hemostasis)
Abstract: In May 2024, the Division of Blood Diseases and Resources of the National Heart, Lung, and Blood Institute (NHLBI) hosted a hybrid workshop on “Extracorporeal membrane oxygenation (ECMO)-induced coagulopathy: strategic initiatives for research and clinical practice.” The event brought together clinicians, scientists, bioengineers, and policymakers to address the challenges of ECMO-associated coagulopathy and explore novel therapeutic approaches. Through expert presentations and collaborative discussions, the workshop focused on innovative anticoagulation strategies, precision medicine, and advanced diagnostics to enhance patient care. The discussions also identified critical research gaps and opportunities for future interdisciplinary collaboration. This summary reviews the current state of knowledge and outlines future research directions for improving ECMO-induced coagulopathy management.